Unruly Souls The Digital Activism of Muslim and Christian Feminists - Peterson, Kristin M. (Rutgers University Press, 2022)
Amid growing digital activism to address gender-based violence, institutional racism, and homophobia in U.S. society, Unruly Souls explores the intersectional feminist activism among young people within Islam and Evangelical Christianity. These religious misfits-marginalized from traditional religious spaces due to their sexuality, gender, or race-employ the creative tactics of digital media in their work to seek justice and to display their fundamental equality in the eyes of God. Through an analysis of various digital projects from hip-hop music videos and Instagram accounts to Twitter hashtags and podcasts, Kristin Peterson argues that the hybrid, flexible, playful, and sensory nature of digital media facilitate intersectional feminist activism within and beyond religious communities. Drawing on work from queer theory, decolonial theory, and Black feminist theory, this study explores how those who have been marginalized are able to effectively deploy their disregarded status along with digital media tactics to cultivate empathetic communities for those recovering from religious trauma